Analisis Hubungan Antara Stres Kerja dan Lingkungan Kerja dengan Turnover Intention: Literatur review - Deddy Novie Citra Arta; Tharsisius Pabendon; Stepanus Sandy; Muh. Abduh. Anwar; Habel Taime (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This article aims to identify the Analysis of the Relationship Between Work Stress and Work Environment with Turnover Intention through an analysis of literature reviews in the field of human resource management. The writing approach in this scientific article is to use qualitative methods and library research with the help of the latest references obtained from Google Schoolers and Mendeley citation searches. The results of the study show that there is a relationship between Work Stress and the Work Environment with Turnover Intention. Where, Work Stress and Work Environment have a positive effect on Turnover Intention in a company. Therefore, in keeping employees from making work transfer requests, the company needs to maintain the mental condition and work environment of employees so that it is more conducive.